Investigating the association between intellectual capital and medium-sized cooperatives performance in Malaysia - Abd Aziz, Mohd Faiq; Mahadi, Nomahaza; Azizul, Muhd. Dhamir Audi; Nordin, Nur Anis; Aujirapongpan, Somnuk (Zhongguo Hangtian Gongye Zonggongsi * Di 3 Yanjiuyuan 31 Yanjiushuo,China Aerospace Corporation, No.3 Third Research Academy, No.31 Institute, 2024)
A cooperative is a business that strives to benefit and support its members through revenue-generating endeavors. Still, the Malaysian cooperative's performance is below average and unchanging. Malaysian cooperatives, despite their long history, are having difficulty surviving and deteriorating short of the intended goals. In addition, the ability of the cooperative to manage its resources in order to achieve sustainable success is correlated with the cooperative's performance. The components of intellectual capital are the strategic resources found in cooperatives: relational, structural, and human capital. Furthermore, how intellectual capital is used affects how well cooperatives perform. Research from the past has also indicated a strong correlation between an organization's performance and its intellectual capital. Furthermore, there exist additional variables that may impact the correlation between intellectual capital and cooperative performance. A total of 250 questionnaires were disseminated using email among cooperatives in Malaysia in order to collect the data; however, only 138 usable responses were gathered and employed for data analysis. Statistical Package for Social Science (SPSS) version 23 and SmartPLS version 3.3.8 were then used to analyze the data in this study using a combination of descriptive and inferential statistics. The results indicated intellectual capital was significantly related to the cooperative performance. It has been demonstrated that high intellectual capital cooperatives operate more effectively because their staff members are better equipped to create, share, integrate, and utilize information inside the company. As a conclusion, the present study is helpful to the managers and policy makers in deciding the optimal level of intellectual capital to enhancing cooperative performance.